Writing the self and exigencies of survival autobiography as catharsis and commemoration - Concepcion, Mary Grace R. (Philippine Studies: Historical and Ethnographic Viewpoints, 2018)
This article discusses the autobiographies written by survivors of Ferdinand Marcos’s martial law regime. Despite incarceration, torture, and the control of writing materials that sought to obliterate the self and the written word, political prisoners undertook great risks to record their lives.interviews with these writers reveal the challenges that, years later, survivors faced in writing their experiences, resulting in the belatedness of autobiographical writing. But in writing and publishing their narratives these activists and political prisoners-turned-writers felt emotional catharsis and empowerment. The passing of their generation has made these survivors realize the acute need to preserve memories of martial law